Functional constipation in infancy and early childhood: epidemiology, risk factors, and healthcare consultation - Anne Willemijn Walter; Anne Hovenkamp; Niranga Manjuri Devanarayana; Roshani Solanga; Shaman Rajindrajith; Marc Alexander Benninga (BMC, 2019)
Abstract Background Functional constipation (FC) is a pediatric problem that is seen frequently. However, its prevalence in Asia remains undetermined. In this study we attempted to determine the prevalence, risk factors and therapeutic modalities of FC in infants and toddlers in Sri Lanka. Methods Children aged 6.5 months to 4 years were selected from 14 well-baby and vaccination clinics in the Gampaha District of Sri Lanka. A questionnaire with questions regarding the socio-demographic characteristics, child's bowel habits, psycho-social risk factors and treatment modalities were filled by the mothers. FC was diagnosed according to ROME III criteria. Results A total of 1113 children were analyzed [(female n = 560 (50.3%) with a mean age of 20.7 months, standard deviation [SD] 11.2 months. FC was found in 89 (8.0%). FC was significantly and independently associated with underweight (14.3% vs 7.2%, p = 0.008. [OR and 95% CI: 2,3 (CI; 1.3-4.2)] and residence in an urban area (9.6% vs 5.6%, p = 0.013). [OR and 95% CI: 0.592 (CI; 0.396-0.95)]. Children subjected to violence showed a significantly higher prevalence of FC (20.0 vs 7.8%, p = 0.046). Children being overweight and children living with mothers subjected to violence showed a higher, though not statistically significant, tendency to develop FC. Children with FC visited healthcare clinics more frequently when compared to controls (19.6% vs 6.0%, p < 0.0001). However, only 24% of infants and toddlers with FC were treated specifically for the condition by a doctor. Conclusions FC occurred in 8% of this cohort of Sri Lankan infants and toddlers. It is significantly associated with underweight and living in an urban area. Only a quarter of them received medical attention for their constipation. Trial registration SLCP/ERC/2014/12, December 2014.